If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -5x = 11 + -8x Solving -16 + -5x = 11 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -16 + -5x + 8x = 11 + -8x + 8x Combine like terms: -5x + 8x = 3x -16 + 3x = 11 + -8x + 8x Combine like terms: -8x + 8x = 0 -16 + 3x = 11 + 0 -16 + 3x = 11 Add '16' to each side of the equation. -16 + 16 + 3x = 11 + 16 Combine like terms: -16 + 16 = 0 0 + 3x = 11 + 16 3x = 11 + 16 Combine like terms: 11 + 16 = 27 3x = 27 Divide each side by '3'. x = 9 Simplifying x = 9
| 4x=12-7x | | y-18=10 | | -16-5x=8x+17 | | x=x-15 | | d(31.9)=3.3x-1.1 | | 2x-5=-7 | | 2x-1=11x-91 | | p(18)=-2.4+6 | | 6d+3(1+d)(d-7)=2d | | s(3)=-4x-9 | | q(21)=6-5x | | 12x-23=8x+5 | | x=3x+(5+3x) | | n(39)=7x+4 | | g(2)=6.1x-2.2 | | 3x+(3x+5)=x | | g(0)=6.1x-2.2 | | g(0)=-9+1 | | 2n+46=9n-10 | | g(-3)=6.1x-2.2 | | x+[(x+10)2]=50 | | 3x+8=6x-19 | | d(2)=-16x+4 | | d(0)=-16x+4 | | d(-3)=-16x+4 | | s(2)=8x-2 | | -6g+12=2g+12 | | s(0)=8x-2 | | s(-3)=.8x-2 | | s(-3)=8x-2 | | -r-5=1-2r | | g(2)=-9(x+1) |